Women's preference for non‐invasive prenatal DNA testing versus chromosomal microarray after screening for Down syndrome: a prospective study. (14th January 2018) - Cheng, YKY; Leung, WC; Leung, TY; Choy, KW; Chiu, RWK; Lo, T‐K; Kwok, KY; Sahota, DS
Abstract : Objective: To examine preferences for follow‐up testing in women screened with high or intermediate risk for Down syndrome in the first or second trimester. Design: Prospective cohort study. Setting: Three public hospitals in Hong Kong, China. Sample: Women with pregnancies termed as high risk (≥1:250; HR) or intermediate risk (1:251–1200; IR) for Down syndrome. Methods: Women with pregnancies screened as HR were offered the choices of: (1) an invasive test plus chromosomal microarray (CMA) to obtain more detailed fetal genetic information; (2) non‐invasive cell‐free prenatal DNA screening (NIPT) to detect trisomies 13, 18 and 21, and to avoid procedure‐related miscarriage; and (3) to decline any further testing. Women received standardised counselling informing them that the reporting times were identical, the procedure miscarriage risk was 0.1–0.2% and that there was no charge for screening. Women with IR pregnancies (1:251–1200) were offered NIPT as a secondary screening test. Main outcome measures: Uptake rate for NIPT. Results: Three hundred and forty‐seven women had pregnancies deemed as HR; 344 (99.1%) women opted for follow‐up testing, 216 (62.2%) of whom chose NIPT. Five hundred and seven of 614 women (82.6%) with IR risk chose NIPT. Seven (21%) of 34 women with nuchal translucency ≥3.5 mm opted for NIPT. Conclusion: In a setting where reporting times are similar and there is no cost difference between options, approximately 60% of women with pregnancies classed as HR would opt for NIPT, offering simple but limited aneuploidy assessment, over a diagnostic procedure with comprehensive and more detailed assessment. Tweetable abstract: 60% of pregnant Chinese women prefer NIPT over CMA when screened as high risk for Down syndrome. Tweetable abstract: 60% of pregnant Chinese women prefer NIPT over CMA when screened as high risk for Down syndrome.